2017
DOI: 10.1038/ncomms15860
|View full text |Cite
|
Sign up to set email alerts
|

Differential processing of thalamic information via distinct striatal interneuron circuits

Abstract: Recent discoveries of striatal GABAergic interneurons require a new conceptualization of the organization of intrastriatal circuitry and their cortical and thalamic inputs. We investigated thalamic inputs to the two populations of striatal neuropeptide Y (NPY) interneurons, plateau low threshold spike (PLTS) and NPY-neurogliaform (NGF) cells. Optogenetic activation of parafascicular inputs evokes suprathreshold monosynaptic glutamatergic excitation in NGF interneurons and a disynaptic, nicotinic excitation thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
126
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(131 citation statements)
references
References 62 publications
5
126
0
Order By: Relevance
“…Furthermore, thalamostriatal synapses exhibit more prominent AMPA receptor‐mediated currents than corticostriatal synapses (Sciamanna et al ., ). We and others have also shown that optogenetic stimulation of terminals from the PfN as well as from cortex was able to induce action potential firing of FSI in mouse striatal slices (Arias‐Garcia et al ., ; Assous et al ., ).…”
Section: Glutamatergic Input To Striatal Interneuronssupporting
confidence: 89%
See 3 more Smart Citations
“…Furthermore, thalamostriatal synapses exhibit more prominent AMPA receptor‐mediated currents than corticostriatal synapses (Sciamanna et al ., ). We and others have also shown that optogenetic stimulation of terminals from the PfN as well as from cortex was able to induce action potential firing of FSI in mouse striatal slices (Arias‐Garcia et al ., ; Assous et al ., ).…”
Section: Glutamatergic Input To Striatal Interneuronssupporting
confidence: 89%
“…Those results, using different manipulations of the PfN, implicate different excitatory and inhibitory components of the CIN response to PfN activation which likely explain the discrepancies. Together with recent data showing that different populations of GABAergic interneurons innervate CINs (English et al ., ) as well as receive monosynaptic inputs from PfN (Assous et al ., ), it seems clear that intrastriatal circuitry plays an critical role in the response of CIN to extrinsic glutamatergic inputs.…”
Section: Glutamatergic Input To Striatal Interneuronsmentioning
confidence: 97%
See 2 more Smart Citations
“…K). These results are consistent with recent studies of the excitatory‐inhibitory control of LTSI activity by PFas projections (Assous et al ., ), but conflict with other anatomical and optogenetic data (Kachidian et al ., ; Ellender et al ., ). The mechanistic basis of these anatomical–physiological discrepancies is currently unclear but could relate to the presence of silent synapses or a sparse distribution of connectivity due to lower density of striatal‐projecting PFas axons or target specificity within patch‐matrix compartments (Herkenham & Pert, ; Deschenes et al ., ).…”
Section: Discussionmentioning
confidence: 97%